Strategi Bertahan Hidup Tukang Becak di Kecamatan Mamajang Kota Makassar - Maulia Phynasti Ekadila; M Nur Zakariyah Leo; Ibrahim Abbas; Alief Saputro (UNM Geographic Journal, 2020)
Pedicab drivers as one of the informal sector professions in the field of transportation services experience socio-economic problems, especially in meeting the needs of family life. This is due to their small and uncertain income in a day. To overcome these economic problems, they carry out various strategies to survive. This study aims to determine; Pedicab Driver Socio-Economic Conditions and Becak Driver Survival Strategies. Data was collected by observation, interviews, questionnaires and documentation. The population of this study was 175 pedicab drivers in Mamajang District with a sample of 44 pedicab drivers. The sampling technique used is the Non-Probability Accidental Sampling technique. The results showed that the adaptive strategy of pedicab drivers in an effort to meet their daily needs was saving family expenses which included; buy cheap groceries, find odd jobs and repair their own rickshaw breakdowns; the use of social networks such as borrowing money when experiencing difficulties, asking for a rickshaw rental fee to be reduced to pedicab owners, cheap rented houses, and the last one is taking advantage of government assistance programs such as BLT, distribution of free basic necessities and school scholarships.